Artificial pumice stone and preparation method thereof

Artificial pumice with honeycomb capillary channels and open pores addresses the low porosity and permeability issues of current filter materials, enhancing liquid storage and adsorption capacity while preventing clogging.

CN119118701AActive Publication Date: 2024-12-13SHENZHEN WUBEN MATERIAL TECHNOLOGY CO LTD

Patent Information

Application Number
CN202411317006.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-20
Publication Date
2024-12-13
Estimated Expiration
2044-09-20

AI Technical Summary

Technical Problem

Current filter materials used in water treatment have low effective porosity and water permeability, leading to clogging and reduced efficiency in liquid storage and adsorption capacity.

Method used

A method to produce artificial pumice with a structure composed of through-type honeycomb capillary channels and open pores, enhancing effective porosity and water permeability by using a mixture of natural clay, silicon-aluminum ratio blending agent, organic and inorganic foaming agents, and directing agents to create a tubular structure with interconnected pores.

Benefits of technology

The artificial pumice achieves high effective porosity (40-60%) and water permeability, reducing the likelihood of blockage and improving liquid absorption and adsorption capacity, with a mass water storage rate of 80-140% and rapid saturation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119118701A_ABST
    Figure CN119118701A_ABST
Patent Text Reader

Abstract

The invention provides an artificial pumice stone and a preparation method thereof, and belongs to the technical field of artificial pumice stones. Foaming is carried out at the temperature of 160-200 DEG C, the organic foaming agent, the inorganic foaming agent and the foaming promoter can generate a large number of bubbles, and a large number of air holes and gaps are formed in the material; in the sintering process, the guiding agent guides accumulation bridging among molecules through a biphenyl structure, a quaternary ammonium group and a biphenyl center provide alkyl linkage which is long enough, capillary self-assembly is guided in a gap, so that a main material is changed into a tubular structure from a layered structure, and the service life of the main material is prolonged. Open air holes can be formed in the material, and capillary tubes communicating the air holes in the material to the surface of the material are arranged through pipelines, so that the effective porosity and water permeability of the artificial pumice stone are improved; by adopting the gas retaining agent, the material can be wrapped, and bubbles generated during foaming are prevented from escaping quickly, so that the effective porosity is improved; the micro-pores and capillary channels of the artificial pumice stone can be further strengthened through activation, and the effective porosity and water permeability are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of artificial pumice production, and in particular relates to an artificial pumice and a preparation method thereof. Background Art

[0002] In water treatment, aerated biological filters need to use filter media to treat organic matter in water bodies and store water. The two main functions of filter media are: one is the filtering and adsorption capacity, and the other is high water permeability and no clogging. These two properties are directly related to the effective porosity of the filter material itself. Most of the current filter materials have low effective porosity, and they are all calculated using the mass ratio (Formula I). ​​Many filter materials use closed pores and have a very low specific gravity, generally between 0.2 and 0.5. Theoretically, the porosity is very high, but the available pores in water treatment are indeed not high, which will cause the system to become clogged and collapse, such as pumice, expanded clay and glass pumice.

[0003] In actual water treatment, the volume calculation method (Formula II) is often used to obtain the effective porosity (volume ratio). The effective porosity represents: the largest spatial liquid storage capacity and the smallest spatial volume loss, a larger specific surface area and better adsorption capacity, more surface tension and flow capacity.

[0004] The calculation formula of the mass specific porosity of the filter material at room temperature is shown in Formula 1:

[0005] The calculation formula of the effective porosity of the filter material at room temperature is shown in Formula II:

[0006]

[0007] In the formula, m1 is the mass of the material when dry, and m2 is the mass of the material after saturation with water;

[0008]

[0009] In the formula, m1 is the mass of the material when dry, m2 is the mass of the material after saturation with water, and V1 is the volume of the material.

[0010] At present, filter media are mainly composed of various porous materials, usually pumice (or zeolite). Pumice is divided into natural pumice and artificial pumice. The performance of natural pumice varies greatly. Most of them have a mass water storage rate of 20% to 50% and an effective porosity of 10% to 20%. Artificial pumice has better performance. Artificial pumice commonly used in water treatment is similar to slag. Its interior is mainly closed pores, and there is no penetrating pipe as a connection, so the actual usable part is very small, usually with a mass water storage rate of 20% to 80% and an effective porosity of 10% to 30%. For ceramsite and glass light stone products, their mass ratio measurement data is usually very high, up to 200%, but the actual usable porosity is very low, generally 10%.

[0011] Water-storage clay is a patent previously applied for by the applicant's technical team. It is a new material developed for artificial wetlands in sponge cities to store rainwater and reuse it. It is characterized by a porous material with a large number of open pores inside. It is very light and has a mass water storage rate of 80% to 110%. However, the effective porosity is only 20% to 30% when calculated by tool volume ratio. The present invention is a new technology that adds honeycomb capillary channels and increases more effective porosity based on this technology.

[0012] In general, most of the filter materials used in current water treatment are made porous on the surface, and the porous specific surface area is used to absorb organic matter in the water. The effective porosity is low, and the liquid only flows in the gaps between the materials, which can easily lead to blockage due to lack of water permeability or poor water permeability. Therefore, how to improve the effective porosity and water permeability of the filter material has become a technical problem that needs to be solved urgently in this field. Summary of the invention

[0013] The purpose of the present invention is to provide an artificial pumice and a preparation method thereof.

[0014] The artificial pumice prepared by the preparation method provided by the present invention is improved on the basis of the traditional porous material into a connection structure composed of a large number of through-type honeycomb capillary channels and a large number of open pores. This structure is to manufacture a large number of pores inside the material while manufacturing a large number of honeycomb capillary channels that penetrate the entire material. These channels simultaneously connect the external space and the pores inside the material. This structure can not only greatly increase the effective porosity in the water treatment process, but also actively absorb the liquid (siphon effect) by utilizing the surface tension of the liquid. At the same time, the structural part connected to the channel on each contacting artificial pumice can also conduct the liquid, which makes the space formed by the material highly permeable, greatly increases the space that can absorb liquid inside the material, and greatly reduces the possibility of blockage, and also brings good adsorption capacity. It is currently the first time that this common material for water treatment appears.

[0015] The honeycomb capillary channels inside the material are mainly composed of silicon oxide and aluminum oxide molecules.

[0016] The effective porosity of the artificial pumice provided by the present invention is embodied in the following aspects:

[0017] 1) Tested by standard impregnation method, the porosity is 40% to 60% (volume ratio), 80% to 140% (mass ratio);

[0018] 2) In the test, each particle can absorb 40% to 60% of its volume of liquid water;

[0019] 3) Specific surface area ≥ 60cm 2 / g(BET method);

[0020] 4) High water permeability.

[0021] The high water permeability of the artificial pumice provided by the present invention is reflected in the following aspects:

[0022] 1) Soak in water at room temperature for one minute and quickly reach saturation;

[0023] 2) No head loss during water permeability testing (simulating aerated biological filter);

[0024] 3) No clogging was found in the long-term use of 200 times in the filtration test;

[0025] 4) In the test under artificial wetland mode, in the summer when the outdoor temperature is 35-40℃, the soil moisture can be maintained at 23-30% without watering for one month.

[0026] At the same time, the increase in effective porosity will also greatly increase the specific surface area, improving the material's ability to adsorb organic matter while also increasing its ability to store liquids in the space.

[0027] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0028] The present invention provides a method for preparing an artificial pumice stone, comprising the following steps:

[0029] (1) mixing a main material, an organic foaming agent, an inorganic foaming agent, a foaming aid, a directing agent, an air retaining agent and water to obtain a slurry; the main material comprises natural clay and / or a silicon-aluminum ratio blending agent; the directing agent comprises a dialkyl quaternary ammonium salt and felbinac;

[0030] (2) foaming and drying the slurry obtained in step (1) in sequence to obtain a blank; the foaming temperature is 160 to 200° C.;

[0031] (3) The blank obtained in step (2) is granulated, sintered and activated in sequence to obtain artificial pumice.

[0032] Preferably, the natural clay in step (1) is water-washed and purified natural clay with a particle size of 100 to 200 meshes.

[0033] Preferably, the silicon-aluminum ratio adjusting agent in step (1) is Al4[Si4O 10 ][OH]8, the purity of the silicon-aluminum ratio adjusting agent is above 95%, and the particle size of the silicon-aluminum ratio adjusting agent is 200-300 mesh.

[0034] Preferably, the organic foaming agent in step (1) is at least one of azodicarbonamide, DPT and peracetic acid, and the organic foaming agent accounts for 0.5-1% of the mass of the main material.

[0035] Preferably, in step (1), the inorganic foaming agent is at least one of sodium bicarbonate, ammonium bicarbonate, and calcium carbide, and the inorganic foaming agent accounts for 1 to 2.5% of the mass of the main material.

[0036] Preferably, the foaming aid in step (1) is alum, and the foaming aid accounts for 0.25-1.5% of the mass of the main material.

[0037] Preferably, the air retaining agent in step (1) is polypropylene alcohol, and the air retaining agent accounts for 0.5-2% of the mass of the main material.

[0038] Preferably, the activator used for activation in step (3) is an aqueous solution of at least one of citric acid, polylactic acid and itaconic acid.

[0039] Preferably, the mass concentration of the activator is 3-5%.

[0040] The present invention also provides artificial pumice prepared by the preparation method described in the above technical solution.

[0041] The invention provides a method for preparing an artificial pumice, comprising the following steps: mixing a main material, an organic foaming agent, an inorganic foaming agent, a foaming aid, a directing agent, an air retaining agent and water to obtain a slurry; the main material comprises natural clay and / or a silicon-aluminum ratio blending agent; the directing agent comprises a dialkyl quaternary ammonium salt and felbinac; the slurry is foamed and dried in sequence to obtain a blank; the foaming temperature is 160-200 DEG C; the blank is granulated, sintered and activated in sequence to obtain the artificial pumice. The invention performs foaming at 160-200 DEG C, and an organic foaming agent, an inorganic foaming agent and a foaming auxiliary agent generate a large number of bubbles, forming a large number of pores and gaps inside the material; during the sintering process, a guiding agent guides the stacking and bridging between molecules through a biphenyl structure, and a quaternary ammonium group and a biphenyl center provide a sufficiently long alkyl link to guide the self-assembly of capillaries in the gap, so that the main material changes from a layered structure to a tubular structure, and can form open pores inside the material and have a capillary that penetrates the pipe to connect the pores inside the material to the surface of the material, thereby improving the effective porosity and water permeability of the artificial pumice; by adopting an air retaining agent, the material can be wrapped to prevent the bubbles generated during foaming from escaping quickly, thereby further improving the porosity of the artificial pumice, and then improving the effective porosity; by sintering, mullite can be realized to improve the strength of the artificial pumice; by activation, the micropores and capillary channels of the artificial pumice can be further strengthened to improve the effective porosity and water permeability. Experimental results show that the mass water storage rate of the artificial pumice prepared by the present invention is 80% to 140%, and the effective porosity is 40% to 60%; the probability of space blockage formed by the artificial pumice is greatly reduced; and the loss of liquid flowing inside is very small, or almost no loss. BRIEF DESCRIPTION OF THE DRAWINGS

[0042] Figure 1 This is a physical picture of the artificial pumice prepared in Example 3;

[0043] Figure 2 This is a SEM image of the artificial pumice prepared in Example 3 magnified 1000 times;

[0044] Figure 3 This is a SEM image of the artificial pumice prepared in Example 3 magnified 5000 times;

[0045] Figure 4 This is a SEM image of the artificial pumice prepared in Example 3 magnified 5000 times;

[0046] Figure 5 This is a test schematic diagram of the artificial pumice prepared in Example 3;

[0047] Figure 6 The water permeability data of the artificial pumice prepared in Example 3. DETAILED DESCRIPTION

[0048] The present invention provides a method for preparing an artificial pumice stone, comprising the following steps:

[0049] (1) mixing a main material, an organic foaming agent, an inorganic foaming agent, a foaming aid, a directing agent, an air retaining agent and water to obtain a slurry; the main material comprises natural clay and / or a silicon-aluminum ratio blending agent; the directing agent comprises a dialkyl quaternary ammonium salt and felbinac;

[0050] (2) foaming and drying the slurry obtained in step (1) in sequence to obtain a blank; the foaming temperature is 160 to 200° C.;

[0051] (3) The blank obtained in step (2) is granulated, sintered and activated in sequence to obtain artificial pumice.

[0052] The present invention has no particular limitation on the sources of the raw materials, and commercially available products known to those skilled in the art may be used.

[0053] The invention mixes the main material, the organic foaming agent, the inorganic foaming agent, the foaming auxiliary agent, the guiding agent, the air retaining agent and water to obtain the slurry.

[0054] In the present invention, the main material includes natural clay and / or a silicon-aluminum ratio adjusting agent; the natural clay is preferably natural clay purified by washing; the particle size of the natural clay is preferably 100-200 mesh; the silicon-aluminum ratio adjusting agent is preferably Al4[Si4O 10 ][OH]8; the purity of the silicon-aluminum ratio adjusting agent is preferably above 95%; the particle size of the silicon-aluminum ratio adjusting agent is preferably 200-300 mesh.

[0055] In the present invention, when the main ingredients are natural clay and a silicon-aluminum ratio blending agent, the natural clay is preferably 40-60% of the main ingredient by mass, more preferably 45-55%, and the silicon-aluminum ratio blending agent is preferably 40-60% of the main ingredient by mass, more preferably 45-55%. The present invention can further improve the effective porosity of artificial pumice by controlling the mass of natural clay and the silicon-aluminum ratio blending agent.

[0056] In the present invention, the organic foaming agent is preferably at least one of azodicarbonamide, DPT and peracetic acid, more preferably azodicarbonamide; the organic foaming agent is preferably 0.5-1% of the mass of the main material, more preferably 0.2-0.8%, more preferably 0.5-0.6%. The present invention limits the amount of the organic foaming agent to the above range to further improve the effective porosity of the artificial pumice.

[0057] In the present invention, when the organic foaming agent is azodicarbonamide, the azodicarbonamide is preferably 0.5-1% of the mass of the main material; when the organic foaming agent is DPT, the DPT is 0.5-1% of the mass of the main material; when the organic foaming agent is peracetic acid, the peracetic acid is 0.1-1% of the mass of the main material.

[0058] In the present invention, the inorganic foaming agent is preferably at least one of sodium bicarbonate, ammonium bicarbonate, hydrogen peroxide and calcium carbide, and more preferably ammonium bicarbonate; the inorganic foaming agent is preferably 1-2.5% of the mass of the main material, more preferably 1.2-2.3%, and more preferably 1.5-2.0%. The present invention limits the amount of the inorganic foaming agent to the above range to further improve the effective porosity of the artificial pumice.

[0059] In the present invention, the foaming aid is preferably alum; the foaming aid is preferably 0.25-1.5% of the mass of the main material, more preferably 0.5-1.2%, and more preferably 0.8-1.0%. The present invention limits the amount of the foaming aid to the above range to further improve the effective porosity of the artificial pumice.

[0060] In the present invention, the guiding agent is a dialkyl quaternary ammonium salt and felbinac acid, preferably a didodecyl dimethyl-γ-diquaternary ammonium salt and felbinac acid; the mass of the guiding agent is preferably 0.08-0.12% of the mass of the main material, more preferably 0.1%; the mass ratio of the dialkyl quaternary ammonium salt to felbinac acid is preferably 1:1. The present invention adds a guiding agent, and during the sintering process, the guiding agent guides the stacking and bridging between molecules through the biphenyl structure, and the quaternary ammonium group and the biphenyl center provide a sufficiently long alkyl link to guide the self-assembly of the capillaries in the gap, so that the main material changes from a layered structure to a tubular structure, and can form open pores inside the material and have capillaries that penetrate the pipes to connect the pores inside the material to the surface of the material, thereby improving the effective porosity and water permeability of the artificial pumice, and then activated by an activator, the performance of the capillary bundle is further enhanced.

[0061] In the present invention, the gas retaining agent is preferably polypropylene alcohol; the gas retaining agent is preferably 0.5-2% of the mass of the main material, more preferably 0.6-1.5%, and more preferably 0.8-1.2%. The present invention uses the gas retaining agent to wrap the material and prevent the bubbles generated during foaming from escaping quickly, thereby further improving the porosity of the artificial pumice and further improving the effective porosity; limiting the amount of the gas retaining agent within the above range can further improve the effective porosity of the artificial pumice.

[0062] The present invention has no particular limitation on the molecular weight of the polypropylene alcohol, and commercially available products known to those skilled in the art may be used.

[0063] In the present invention, the water is preferably 30-70% by mass of the main material, more preferably 50-60% by mass.

[0064] In the present invention, the mixing of the main material, the organic foaming agent, the inorganic foaming agent, the foaming aid, the guiding agent, the air retaining agent and water preferably comprises the following steps:

[0065] 1) mixing an organic foaming agent and a foaming aid to obtain a first mixed material;

[0066] 2) mixing the main material, the first mixed material obtained in step 1), an inorganic foaming agent and a directing agent to obtain a second mixed material;

[0067] 3) mixing the air retaining agent and water to obtain an air retaining agent solution;

[0068] 4) mixing the second mixed material obtained in step 2) and the air retaining agent solution obtained in step 3);

[0069] There is no order of precedence for steps 1) to 2) and step 3).

[0070] In the present invention, the organic foaming agent and the foaming aid are preferably mixed to obtain a first mixed material.

[0071] The present invention has no special limitation on the mixing operation of the organic foaming agent and the foaming aid, and the technical scheme for preparing the mixed material well known to those skilled in the art can be adopted.

[0072] After obtaining the first mixed material, the present invention preferably mixes the main material, the first mixed material, the inorganic foaming agent and the directing agent to obtain the second mixed material.

[0073] The present invention has no special limitation on the operation of mixing the main material, the first mixed material, the inorganic foaming agent and the directing agent, and the technical scheme for preparing the mixed material well known to those skilled in the art can be adopted.

[0074] In the present invention, the air retaining agent and water are preferably mixed to obtain an air retaining agent solution.

[0075] The present invention has no special limitation on the operation of mixing the air retaining agent and water, and the technical scheme for preparing the mixed material well known to those skilled in the art can be adopted.

[0076] After obtaining the second mixed material and the gas retaining agent solution, the present invention preferably mixes the second mixed material and the gas retaining agent solution.

[0077] The present invention has no special limitation on the operation of mixing the second mixed material and the gas retaining agent solution, and a technical solution for preparing a mixed material well known to those skilled in the art may be used.

[0078] After the mixing is completed, the present invention preferably ages the mixed product to obtain a slurry.

[0079] In the present invention, the aging temperature is preferably room temperature; the aging time is preferably 12 to 24 hours, more preferably 15 to 24 hours. The present invention can fully infiltrate through aging.

[0080] After obtaining the slurry, the present invention sequentially foams and dries the slurry to obtain a blank. The present invention performs foaming at 160-200° C., and the organic foaming agent, the inorganic foaming agent and the foaming aid generate a large number of bubbles, forming a large number of pores and gaps inside the material.

[0081] In the present invention, the foaming temperature is 160-200°C, more preferably 170-180°C; the foaming time is preferably 50-120 minutes, more preferably 60-100 minutes. The present invention can quickly increase the temperature of the mud material by foaming at high temperature, so that the foaming agent can fully react in a short time to generate a large number of bubbles; the effective porosity of the artificial pumice can be further improved by controlling the temperature and time of the foaming.

[0082] The present invention has no special limitation on the drying operation, as long as the moisture content of the blank is controlled below 10%.

[0083] After the blank is obtained, the present invention sequentially granulates, sinters and activates the blank to obtain artificial pumice.

[0084] In the present invention, the blank is preferably cut before granulation. The present invention has no special limitation on the cutting operation, and the operation well known to those skilled in the art can be adopted. The cutting in the present invention is beneficial to the subsequent granulation.

[0085] The present invention has no particular limitation on the granulation operation, and any operation well known to those skilled in the art may be used.

[0086] In the present invention, the particle size obtained by granulation is preferably 0.5 to 1.5 cm, more preferably 0.5 to 1 cm or 1 to 1.5 cm.

[0087] In the present invention, the sintering temperature is preferably 800-1000°C, more preferably 850-900°C; the sintering time is preferably 60-90 minutes, more preferably 60-70 minutes. The present invention can achieve mullite by sintering, thereby improving the strength of artificial pumice; during the sintering process, the directing agent guides the stacking and bridging between molecules through the biphenyl structure, and the quaternary ammonium group and the biphenyl center provide a sufficiently long alkyl link to guide the capillary self-assembly in the gap, so that the main material changes from a layered structure to a tubular structure, and can form open pores inside the material and have capillaries that penetrate the pipe to connect the pores inside the material to the surface of the material, thereby improving the effective porosity and water permeability of the artificial pumice.

[0088] In the present invention, the activator used for the activation is preferably an aqueous solution of at least one of citric acid, polylactic acid and itaconic acid; the mass concentration of the activator is preferably 3-5%, more preferably 3.5-4.0%. The present invention has no special limitation on the amount of the activator, as long as the calcined product is completely immersed in the activator.

[0089] In the present invention, the activation temperature is preferably room temperature; the activation time is preferably greater than 10 minutes, more preferably 12 to 20 minutes, and more preferably 15 minutes. The present invention can precipitate impurities in the material through activation to obtain pure material, thereby further strengthening the micropores and capillaries of the artificial pumice and improving the effective porosity.

[0090] After activation is completed, the present invention preferably washes the product obtained by activation with water to obtain artificial pumice.

[0091] The present invention has no particular limitation on the water washing operation, and any operation well known to those skilled in the art may be used.

[0092] The present invention also provides artificial pumice prepared by the preparation method described in the above technical solution.

[0093] In the present invention, the interior of the artificial pumice is a structure in which micropores and through-type pipes are combined.

[0094] The artificial pumice of the present invention is a porous material combining silicon and carbon elements. Its exterior is similar to conventional porous materials, and its interior is a structure combining micropores and through-type pipes. This structure can form a considerable number of gaps inside the material. In the liquid, these gaps and the surface tension of the liquid combine to allow the liquid to flow freely inside the material, similar to the siphon effect, thereby improving the water permeability inside the material.

[0095] In the present invention, the shape of the artificial pumice is preferably porous block, brecciated, pebble, sphere, column or powder.

[0096] In the present invention, the physical parameters of the artificial pumice are:

[0097] Bulk density: 0.33-0.67 tons / cubic meter;

[0098] Specific surface area: ≥60cm 2 / g;

[0099] Porosity: 40-60%;

[0100] Quality water storage rate: 80%~140%;

[0101] Effective porosity: 40% to 60%;

[0102] Cylinder pressure strength: 0.5~2MPa

[0103] Appearance: white, khaki, reddish brown or off-white; spherical or ellipsoidal;

[0104] Particle size: 5-15mm;

[0105] Composition: Silicon oxide, aluminum oxide or iron oxide.

[0106] The present invention simulates the formation principle of volcanic rocks and produces an artificial pumice containing a large number of micropores and capillaries, which can not only store a large amount of flowable liquid, but also utilize the siphon effect of the capillaries to maintain the fluidity of the liquid therein so that it will not be blocked, thereby greatly improving the performance of the artificial pumice and greatly reducing the manufacturing cost of the artificial pumice. This characteristic allows it to be used for water purification, artificial wetlands, soil improvement and agricultural production in arid areas.

[0107] The artificial pumice provided by the present invention adds a large number of capillary channels of honeycomb tube bundle structure on the basis of original water-storing clay, connects the pores and the outside of the material, ensures the maximum liquid storage capacity and water permeability inside the material, can improve the effect and efficiency of water treatment and save costs, has a mass water storage rate of 80-140%, and an effective porosity of 40-60%, and is the porous material with the highest liquid storage capacity. After stacking, the spatial water storage rate can reach 70%, of which 30-40% is water storage between particles and 40-50% is water storage inside the material.

[0108] The artificial pumice provided by the present invention has open pores inside and has through-pipes connecting the pores inside the material to the surface of the material, so that the material has a very strong ability to absorb liquids. It can absorb water to reach a saturated state within one minute, and can also output internal water to the surface under appropriate circumstances; it has more external and internal specific surface areas, so that its ability to absorb organic matter in water is improved.

[0109] The technical solutions in the present invention will be described clearly and completely below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0110] The natural clay used in the embodiment is natural clay washed by river water in Guangdong area.

[0111] Example 1

[0112] A method for preparing artificial pumice comprises the following steps:

[0113] (1) 100 mesh washed natural clay and 300 mesh dried Al4[Si4O 10 ][OH]8 to obtain ingredient 1; wherein the washed natural clay is washed natural clay and Al4[Si4O 10 ][OH]8 40% of the total mass, Al4[Si4O 10 ][OH]8 is water-washed natural clay and Al4[Si4O 10 ][OH]8 60% of the total mass;

[0114] (2) mixing 1% by weight of azodicarbonamide in ingredient 1 with 1.5% by weight of alum in ingredient 1 to obtain a first mixed material;

[0115] (3) placing 2.5% by weight of ammonium bicarbonate of ingredient 1, 0.05% by weight of didodecyl dimethyl-γ-diquaternary ammonium salt of ingredient 1, and 0.05% by weight of felbinac of ingredient 1, ingredient 1, and the first mixed material in a dry powder mixer and mixing for 15 minutes to obtain a second mixed material;

[0116] (4) selecting 60% water of ingredient 1 by weight, adding 2% polypropylene alcohol-2000 of ingredient 1 by weight, and mixing in a liquid mixer to obtain an air retaining agent solution;

[0117] (5) putting the second mixed material and the air retaining agent solution into a mud mixer and stirring for 15 minutes to obtain a slurry;

[0118] (6) The slurry was aged for 24 hours, then foamed at 200° C. for 60 minutes, and then dried to a moisture content of less than 10% to obtain a blank;

[0119] (7) Cut the blank into small pieces with a diameter of 1 cm*1 cm*1 cm, and then put them into a disc granulator for granulation to obtain spheres with a diameter of 1 cm;

[0120] (8) The spheres were sent to a sintering furnace at 850° C. for solidification for 60 min, then immersed in a 3.5% citric acid aqueous solution for activation for 15 min, and washed with water to obtain artificial pumice.

[0121] Example 2

[0122] A method for preparing artificial pumice comprises the following steps:

[0123] (1) mixing 0.5% by weight of azodicarbonamide and 0.5% by weight of alum of the washed natural clay to obtain a first mixed material;

[0124] (2) placing 1.0% of ammonium bicarbonate by weight of the washed natural clay, 0.05% of didodecyl dimethyl-γ-diquaternary ammonium salt by weight of the washed natural clay, 0.05% of felbinac by weight of the washed natural clay, the washed natural clay, and the first mixed material in a dry powder mixer and mixing for 15 minutes to obtain a second mixed material; wherein the particle size of the washed natural clay is 100 mesh;

[0125] (3) selecting 30% water by weight of the washed natural clay, adding 0.5% polypropylene alcohol-2000 by weight of the washed natural clay into a liquid mixer and mixing to obtain an air retaining agent solution;

[0126] (4) putting the second mixed material and the air retaining agent solution into a mud mixer and stirring for 15 minutes to obtain a slurry;

[0127] (5) The slurry is placed for 24 hours for aging, then foamed at 200° C. for 120 minutes, and then dried to a moisture content of less than 10% to obtain a blank;

[0128] (6) Cut the blank into small pieces with a diameter of 1 cm*1 cm*1 cm, and then put them into a disc granulator for granulation to obtain spheres with a diameter of 1 cm;

[0129] (7) The spheres were sent to a sintering furnace at 1000° C. for solidification for 90 min, then immersed in a 3% citric acid aqueous solution for activation for 15 min, and washed with water to obtain artificial pumice.

[0130] Example 3

[0131] A method for preparing artificial pumice comprises the following steps:

[0132] (1) 100 mesh washed natural clay and 95% purity and 200 mesh dried Al4[Si4O 10 ][OH]8 to obtain ingredient 1; wherein the washed natural clay is washed natural clay and Al4[Si4O 10 ][OH]8 accounts for 45% of the total mass, Al4[Si4O 10 ][OH] is water-washed natural clay and Al4[Si4O 10 ][OH]8 55% of the total mass;

[0133] (2) mixing 1% by weight of azodicarbonamide in ingredient 1 with 1% by weight of alum in ingredient 1 to obtain a first mixed material;

[0134] (3) placing 1.5% by weight of ammonium bicarbonate of ingredient 1, 0.05% by weight of didodecyl dimethyl-γ-diquaternary ammonium salt of ingredient 1, 0.05% by weight of felbinac of ingredient 1, ingredient 1 and the first mixed material in a dry powder mixer and mixing for 15 minutes to obtain a second mixed material;

[0135] (4) selecting 40% water of ingredient 1 by weight, adding 1.5% polypropylene alcohol-2000 of ingredient 1 by weight into a liquid mixer and mixing to obtain an air retaining agent solution;

[0136] (5) putting the second mixed material and the air retaining agent solution into a mud mixer and stirring for 15 minutes to obtain a slurry;

[0137] (6) The slurry was aged for 24 hours, then foamed at 200° C. for 60 minutes, and then dried to a moisture content of less than 10% to obtain a blank;

[0138] (7) Cut the blank into small pieces with a diameter of 1 cm*1 cm*1 cm, and then put them into a disc granulator for granulation to obtain spheres with a diameter of 1 cm;

[0139] (8) The spheres were sent to a 900° C. sintering furnace for solidification for 90 min, and then immersed in a 3% mass concentration citric acid aqueous solution for activation for 15 min. After washing with water, artificial pumice was obtained.

[0140] The actual picture of the artificial pumice prepared in Example 3 is as follows Figure 1 shown.

[0141] from Figure 1 It can be seen that the prepared artificial pumice is ellipsoidal.

[0142] The SEM image of the artificial pumice prepared in Example 3 is as follows: Figures 2 to 4 As shown; among them, Figure 2 This is a SEM image of the artificial pumice prepared in Example 3 magnified 1000 times; Figure 3 and 4 All are SEM images of the artificial pumice prepared in Example 3 at a magnification of 5000 times.

[0143] from Figures 2 to 4 It can be seen that the artificial pumice prepared in the example has a large number of capillary channels and pores mixed together to form a structure in which the through-type channels and pores are connected.

[0144] Comparative Example 1

[0145] Industrially produced artificial pumice (6,000 yuan / ton)

[0146] Comparative Example 2

[0147] Water storage clay (CN1218904C)

[0148] The performance tests of the artificial pumice prepared in Examples 1 to 3 and Comparative Examples 1 to 2 are shown in Table 1, wherein the mass water storage rate and the effective porosity (volume water storage rate) are tested by the standard immersion method (calculated with clean water at normal temperature and pressure); the cylinder compressive strength is tested by the national standard GB2842-81 "Test method for lightweight aggregates", and the following are all average values.

[0149] Table 1 Performance data of artificial pumice prepared in Examples 1 to 3 and Comparative Examples 1 to 2

[0150] project Example 1 Example 2 Example 3 Comparative Example 1 Comparative Example 2 Mass water storage rate / % 140 80 120 30~80 80~100 Effective porosity / % 60 40 53 10~30 20~30 Cylinder pressure strength / MPa 0.5 2 1 2~3 0.3~0.5

[0151] It can be seen from Table 1 that the artificial pumice prepared by the present invention has good effective porosity and mass water storage rate; in addition, the artificial pumice prepared by the present invention has excellent cylinder pressure strength.

[0152] Water permeability test

[0153] 1. The artificial pumice prepared in Examples 1 to 3 and Comparative Examples 1 to 2 were tested for saturated adsorption time (water adsorption). The results are shown in Table 2.

[0154] Table 2 Saturated adsorption time data of artificial pumice prepared in Examples 1 to 3 and Comparative Examples 1 to 2

[0155] project Example 1 Example 2 Example 3 Comparative Example 1 Comparative Example 2 Saturated adsorption time 30s 200s 60s 30~60min 200~300s

[0156] It can be seen from Table 2 that the artificial pumice prepared by the present invention can actively absorb liquid (siphon effect) by utilizing the surface tension of the liquid, thereby being able to perform saturated adsorption in a relatively short time.

[0157] 2. Strong fluidity test (simulating BAF aerated biological filter)

[0158] The strong fluidity of the artificial pumice prepared in Example 3 (in the structure of a large number of open pores + penetrating capillary channels, the liquid will flow rapidly in the channels and pores due to surface tension, so the liquid is actually flowing continuously in the space formed by the material) was tested. A water pump was used to inject water into the bottom of the container at a fixed height position through a pipe inserted at the bottom with the same power. The total amount of water flow and the time when the water level reached the four standard positions of the container were measured by a floor scale and a timer to calculate the flow rate of water in the space filled with different particles. The three modes of this test were: no material filling, 5-10 mm particles filling, and 10-15 mm particles filling. In the mode of no filler filling, 4.15 m took 1 hour, and the water volume test was 302 kg. The test method is as follows Figure 5 shown.

[0159] The water permeability data of the artificial pumice prepared in Example 3 are as follows: Figure 6 shown.

[0160] from Figure 6 It can be seen that the probability of space blockage formed by the artificial pumice prepared by the present invention is greatly reduced; the loss of liquid flowing inside is very small, almost no loss.

[0161] 3. Long-term effect

[0162] The artificial pumice prepared in Example 3 was used for 200 times in the filtration test without any clogging.

[0163] In summary, the artificial pumice prepared by the present invention has excellent water permeability.

[0164] The carbon content of the artificial pumice prepared in Example 3 was tested, and the results are shown in Table 3.

[0165] Table 3 Carbon content of artificial pumice prepared in Example 3

[0166] project method C(%) Artificial pumice 5mg standard sample method 0.14

[0167] As can be seen from Table 3, the carbon content of artificial pumice is relatively low.

[0168] The artificial pumice prepared in Example 3 was subjected to a component analysis test; the instrument model was an X-ray fluorescence spectrometer ARL Perform'X, and the instrument number was 21003415; the test was based on JY / T0569-2020 General Rules for Wavelength Dispersion X-ray Fluorescence Spectrometric Analysis Methods; the test method was to add artificial pumice and boric acid to a tablet press, press them into a round block with a diameter of 40 mm, a thickness of 3 mm, and a smooth and flat surface, and then place the round block in a sample holder and into the instrument sample feed position, fill in the sample information on the instrument software, start the test, and export the test data after the test is completed. The XRF component analysis results showed that the main components were SiO2, Al2O3, K2O, and Fe2O3, with contents of 52.11%, 39.09%, 3.07%, and 2.70%, respectively.

[0169] It can be seen from the above embodiments and comparative examples that the artificial pumice prepared by the preparation method provided by the present invention has high effective porosity and high water permeability.

[0170] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing an artificial pumice stone comprises the following steps: (1) mixing a main material, an organic foaming agent, an inorganic foaming agent, a foaming aid, a directing agent, an air retaining agent and water to obtain a slurry; the main material comprises natural clay and / or a silicon-aluminum ratio blending agent; the directing agent comprises a dialkyl quaternary ammonium salt and felbinac; (2) foaming and drying the slurry obtained in step (1) in sequence to obtain a blank; the foaming temperature is 160 to 200° C.; (3) The blank obtained in step (2) is granulated, sintered and activated in sequence to obtain artificial pumice.

2. The preparation method according to claim 1, characterized in that: The natural clay in step (1) is water-washed and purified natural clay with a particle size of 100 to 200 meshes.

3. The preparation method according to claim 1, characterized in that: The silicon-aluminum ratio adjusting agent in step (1) is Al4[Si4O 10 ][OH]8, the purity of the silicon-aluminum ratio adjusting agent is above 95%, and the particle size of the silicon-aluminum ratio adjusting agent is 200-300 mesh.

4. The preparation method according to claim 1, characterized in that: In the step (1), the organic foaming agent is at least one of azodicarbonamide, DPT and peracetic acid, and the organic foaming agent accounts for 0.5-1% of the mass of the main material.

5. The preparation method according to claim 1, characterized in that: In the step (1), the inorganic foaming agent is at least one of sodium bicarbonate, ammonium bicarbonate, hydrogen peroxide and calcium carbide, and the inorganic foaming agent accounts for 1 to 2.5% of the mass of the main material.

6. The preparation method according to claim 1, characterized in that: In the step (1), the foaming aid is alum, and the foaming aid accounts for 0.25-1.5% of the mass of the main material.

7. The preparation method according to claim 1, characterized in that: In the step (1), the air retaining agent is polypropylene alcohol, and the air retaining agent accounts for 0.5-2% of the mass of the main material.

8. The preparation method according to claim 1, characterized in that: The activator used for activation in step (3) is an aqueous solution of at least one of citric acid, polylactic acid and itaconic acid.

9. The preparation method according to claim 8, characterized in that: The mass concentration of the activator is 3-5%.

10. Artificial pumice prepared by the preparation method according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Preparation process for aluminosilicophosphate molecular sieve

    CN102424399A

  • Porous composite mineral water purification material and preparation method thereof

    CN117816123A

  • Water storing, foamed China clay and is preparing method

    CN1480428A

  • Mullite-based micro-nano-porous heat insulating refractory material and preparation method therefor

    WO2022144014A1

Cited By

  • Artificial pumice stone and preparation method therefor

    WO2026061364A1